THE PROBLEM OF EMOTIONAL STABILITY OF THE EDUCATOR IN SPECIAL INSTITUTIONS OF PRESCHOOL EDUCATION - Войтович, Оксана (SWorldJournal, 2024)
The subject of the article is the analysis of the problem of the quality of the emotional sphere, which is formed in the future educator of a special preschool educational institution, in particular the special aspects of its development in the preparing